Livestock Guarding Dogs Shape Activity Patterns of Sympatric Mesocarnivores in Sheep Ranches of the Patagonia Region - Moreira-Arce, D (Elsevier GmbH, 2024)
Predation of livestock by wild carnivores is a source of human-wildlife conflict. Livestock Guarding Dogs (LGDs) are one of the most effective non-lethal methods used. LGDs could impact wildlife due to their possible top predator role; their effect on mesocarnivores has been studied mainly in terms of space use, however, temporal effects may also exist. Our study sought to determine the possible effects of LGD presence on the activity patterns of the native foxes Lycalopex griseus and L. culpaeus in southern Chile. Activity patterns were estimated from fox detections with camera traps set on ranches with and without LGDs in Isla Riesco, Magallanes region, Chile, between 2016 and 2018. We quantified the activity patterns of each fox species in presence/absence of LGDs, and under different conditions including breeding vs non-breeding season, moon phase and vegetation cover. Both species modified their daily activity pattern, avoiding times of day of high LGD activity; nevertheless, these modifications did not change the temporal interaction between the native foxes. Activity patterns of foxes without LGDs did not differ from those in natural areas. The effect of LGDs on fox activity patterns was stronger than other ecological variables (breeding season, moon phase or vegetation cover). Since LGDs change the activity patterns of foxes, they cannot be seen as a totally innocuous predation control tool; however, carnivores’ temporal avoidance of areas with a fear-evoking agent like LGDs would result in fewer livestock-predators encounters, thus reducing sheep predation risk. LGDs appear to exert non-lethal effects upon carnivores that would contribute to reduced predation rates and may help decrease producers’ economic losses, as well as the retaliatory hunting of wild carnivores. Thus, our results support that LGDs could be contributing to the co-existence with native predators in areas destined for livestock production. © 2024 Elsevier GmbH